Hubungan Fasilitas Perpustakaan Sekolah dengan Minat Baca Siswa Kelas V SD Gugus 32 Kecamatan Citta - Rosmalah Rosmalah; Muhammad Irfan; Andi Murnianti; Makmur Nurdin (Jurnal Pendidikan dan Pembelajaran Sekolah Dasar (JPPSD), 2022)
The problem in this research is the lack of interest in reading students is influenced by inadequate school library facilities. This study is a quantitative study with a correlation design that aims to determine the relationship between school library facilities and reading interest in fifth grade students of SD Gugus 32, Citta District, Soppeng Regency.. The results showed that there was a significant relationship between school library facilities and reading interest in fifth grade students of SD Gugus 32, Citta District, Soppeng Regency. with ???????????????????????? (3.7497) greater (>) the value of ???????????????????????? (1.67655) which means ????0 is rejected and ????1 is accepted. Based on the analysis of the data above, it can be concluded that school library facilities will have an impact on students' reading interest so that it will affect students' reading habits. So, the better the school library facilities, the more students' reading interest will be. From these conclusions, the impact resulting from this study is known that good school library facilities will increase students' reading interest.